Development of Wordwall Application-based Tajweed Teaching Materials for Baitul Haq TPA Students Makam Haji Sukoharjo's - Sukmaningtyas, Anisa Nur Izzati; Lubis, Ibrahim Siddiq; Anshara, Jessenia Hayfa; Masngud, Muhammad Ibnu; Nurrohim, Ahmad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study is based on the results of observations and interviews conducted on several elementary school students who attended the afternoon al-Quran Education (TPA) park at the Baitul Haq Makam Haji mosque, Surakarta that during the process of delivering tajweed material teachers only use the lecture method, where the classical method only delivers material using oral and students listen to it. As a result, this method does not involve students so it is felt that this method is less effective for tajweed material which is the main support in learning the Quran. Based on these facts, researchers then conducted a study aimed at the effectiveness, practicality and validity of interactive multimedia-based "tajweed" teaching materials for elementary school students on learning the Quran. The model used in this development research is ADDIE. There are 5 stages carried out, namely analysis, design, development, implementation, and evaluation. The method was chosen to achieve the research objective, namely the effectiveness of this interactive multimedia-based learning method.